CONTENT OF TEACHING PROFESSIONALLY ORIENTED WRITTEN COMMUNICATION - I. I. Antonenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article is devoted to the problems of teaching foreign languages in non-linguistic universities in the process of professional education. Special attention is paid to teaching professionally oriented written communication in English and developing professional communicative competence of students, defining components in the system of teaching foreign languages for professional communication, content and objectives of teaching foreign languages to future specialists in the publishing and printing industry. This article examines the genre and cognitive-communicative approaches, analyzes the notions of genre and genre competence and defines their place in the methodology of teaching writing. It stresses the importance to motivate students and to create favorable learning conditions for mastering educational and professional material and to encourage intellectual development and creativity of students. The usefulness of genre approach in teaching students and in the selection of materials for teaching writing in English is explained. The groups of genres that are typical for written communication of future specialists and the classification of genres of the periodical press are analyzed.